ANALISIS ASUHAN KEPERAWATAN PADA LANSIA YANG MENGALAMI KECEMASAN DENGAN INTERVENSI INOVASI RELAKSASI OTOT PROGRESIF DI WILAYAH KELURAHAN PASEBAN, JAKARTA PUSAT - Fuziana Dzulhia Putri (2023)
Elderly people who suffer from hypertension will feel more anxious in themselves caused by certain factors such as worry about their illness and health which can cause anxiety. This case study of nurses' scientific work aims to examine the effect of innovative progressive muscle relaxation therapy in overcoming anxiety in the elderly who suffer from hypertension in the Paseban Village Region. The case study involved two elderly people with moderate anxiety levels, and the Hamilton Rating Scale Anxiety (HARS) instrument was used to measure anxiety levels. The results showed that the administration of progressive muscle relaxation therapy resulted in a decrease in anxiety scores in both patients. Treated patients experienced a 10 point decrease in score from 23 to 13, while resume patients experienced a score decrease of 8 points from 18 to 10. These findings prove that progressive muscle relaxation therapy is effective in reducing anxiety levels in elderly people with hypertension. In this study, it is also suggested that patients get support from their families in implementing progressive muscle relaxation therapy as part of a holistic and sustainable treatment.